Numerical study and development of component model for the behaviour of rigid beam-column joints in steel structures for progressive collapse - Oh, Kai Siang (2016)
The risk of progressive collapse has been an increasing concern after the Ronan Point incident, even more so after the World Trade Centre incident. In blast events, load-bearing structural elements (e.g. columns) may be destroyed to a degree where it cannot sustain anymore load. This means that the remaining components will be subjected to extreme loadings. If the robustness of the components is insufficient to sustain the loads, progressive collapse is likely to occur. This report investigates the behaviour of a bare steel WUF-B connection when subjected to extreme loadings (i.e. column loss scenario). In order to better understand the behaviour, numerical analyses were done and validated with the experimental results from literature review. Parametric studies were then conducted to explore the effects of different parameters on the overall behaviour. The parameters were: beam span, bolt diameter, end distance and fin-plate thickness. The results showed that beam span and fin-plate thickness had the greatest effect on the joint’s behaviour. But although longer beam span results in higher resistance, it is still not a good option as it also reduces the joint’s rotational capacity. The best option to improve the connection would be to increase fin-plate thickness or use a stronger material for the fin-plate which increased both the resistance and rotational capacity of the joint. The effects of bolt diameter and end distance were not significant and thus should not be considered. Next, a component method was proposed to the connection to account for the effects of catenary action. The WUF-B connection was broken down into two main components: unit bolt row connection and beam flange component. The constitutive behaviour of the components were formulated using a spreadsheet and then validated with experimental results from the literature review and the finite element model using CONNECTOR elements in ABAQUS. The validation proved that the component method can serve as a more efficient alternative to finding out the behaviour of the connection under column removal.